Characteristics of Firms Violating Annual Financial Disclosure Timing: The Case of Jordan - Saaydah, Mansour I. (International Journal of Economics and Financial Issues, 2017)
The objective of this study is to identify the characteristics of firms violating annual financial disclosure timing set by the Jordan Securities Commission (JSC). Sample firms average size, profitability indicators, total assets turnover, cash dividend per share and share market to book value were compared to industry-wide averages The study sample consists of all companies disclosed on the JSC sight as not providing their 2012 annual reports on time or provided reports with missing significant disclosure items and warned from further penalties by the commission. The study data on twenty six companies (divided into three sub-samples: 8 manufacturing, 7 service and 11 financial) who violated disclosure requirement was obtained, mostly, from the official audited Jordanian public shareholding companies guide for 2013. The sample company 2012 variables were subject to the one sample T-tests to find out if there are significant mean differences from industry-wide averages for the same year. Results of the manufacturing firms sub-sample indicate less average net operating profit, less profitability (based on return on assets), less cash dividend per share and lower share market to book value. However, the averages of firm size (market value), total assets turnover, earnings per share, and return on equity are all lower than the manufacturing industry-wide averages in 2012, but not in a significant way. Results of service firms’ sub-sample, show only significant lower average cash dividend per share compared to average industry-wide service firm in 2012. Results of financial firms sub-sample show significant lower average total assets, less earnings per share and cash dividend per share than average industry-wide financial firm in 2012. The overall conclusion is that Jordanian industrial and financial firms who file their annual reports late or misfile certain important disclosure items underperform average company’s profitability and cash dividend per share relative to their respective sectors. Keywords: Financial disclosure timing, Jordan securities commission, Profitability, Cash Dividends, Good news Bad news. JEL Classifications: D53, E44, G2